Función social del intelectual - Cámere, Edistio (Mercurio Peruano, 2013)
This article addresses the intellectual's mission in modern society. His/Her talent should not lead him/her to self-indulgence or to have an approach in life that is concerned about his sole particular well-being. Careful and sensible observation of social phenomena, together with a capacity for deep, down-to-earth reflection, will undoubtedly enable the intellectual not only to communicate accurately with his/her peers but also with any ordinary person who requires ideas for enlightenment or for decision-making. The intellectual's social role is a clear contribution to the common well-being of humanity since it provides alternatives where there seem to be no options or where gloom and despondency seem to thrive.
Keywords: intellectual, to observe, to think, communication, social benefit